Influence of organic modification on mechanical properties of melt processed intercalated poly(methyl methacrylate)-organoclay nanocomposites - Tiwari, Rajkiran R.; Natarajan, Upendra (Journal of Applied Polymer Science, 2007)
The influence of organic modifiers on intercalation extent, structure, thermal and mechanical properties of poly(methyl methacrylate) (PMMA)-clay nanocomposites were studied. Two different organic modifiers with varying hydrophobicity (single tallow versus ditallow) were investigated. The nanocomposites were prepared from melt processing method and characterized using wide angle X-ray diffraction, transmission electron microscopy, thermogravimetric analysis, differential scanning calorimetry (DSC), and tensile tests. Mechanical properties such as tensile modulus (E), break stress (sigma(brk)), and 0% break strain (epsilon(brk)) were determined for nanocomposites at various clay loadings. Extent of PMMA intercalation is sufficient and in the range 9-15 angstrom depending on organoclay and filler loading. Overall thermal stability of nanocomposites increases by 16-30 degrees C. The enhancement in T-g of nanocomposite is merely by 2-4 degrees C. With increase in clay loading, tensile modulus increases linearly while % break strain decreases. Break stress is found to increase till 4 wt % and further decreases at higher clay loadings. The overall improvement in thermal and mechanical properties was higher for the organoclay containing organic modifier with lower hydrophobicity and single tallow amine chemical structure. (c) 2007 Wiley Periodicals, Inc.
Keywords: mechanical properties; Nanocomposites; organoclay; structure; Thermal properties

New poly(phenylene oxide)/polystyrene blend nanocomposites with clay: intercalation, thermal and mechanical properties - Tiwari, Rajkiran R.; Khilar, Kartic C.; Natarajan, Upendra (Journal of Applied Polymer Science, 2008)
We present the first study and results on the preparation and characterization of montmorillonite clay filter based polymer blend nanocomposites of the miscible poly(phenylene oxide)/polystyrene blend. Intercalated nanocomposites, prepared by a melt-processing method with 2-6 wt % commercially available organically modified sodium montmorillonite, have been characterized with wide-angle X-ray diffraction, transmission electron microscopy analysis, thermal analysis (thermogravimetric analysis and differential scanning calorimetry), and mechanical tensile tests. We show that nanocomposites can be successfully prepared in a batch mixer at temperatures much below the conditions conventionally used for this blend without organic degradation. Thermal stability is enhanced by nanoscale hybrid formation. The level of intercalation (change in the d-spacing) does not change with the clay loading. Better dispersion of clay in the blend matrix has been observed at a low level of clay content. The nanocomposites show improved tensile modulus (by 31%) in comparison to the blend, whereas the tensile strength (stress at break) and elongation decrease in the presence of the filler with an increase in the clay loading. The Halpin-Tsai model is able to predict the modulus of the nanocomposites in very good agreement with the experimental data. (c) 2008 Wiley Periodicals, Inc.
Keywords: mechanical properties; Nanocomposites; organoclay; poly(phenylene oxide); Polystyrene; Thermal properties

Thermal and mechanical properties of melt processed intercalated poly(methyl methacrylate)-organoclay nanocomposites over a wide range of filler loading - Tiwari, Rajkiran R.; Natarajan, Upendra (Polymer International, 2008)
BACKGROUND: Poly(methyl methacrylate) (PMMA)-organoclay nanocomposites with octadecylammonium, ion-modified montmorillonite, prepared via melt processing, over a wide range of filler loading (2-16 wt%) were investigated in detail. These hybrids were characterized for their dispersion structure, and thermal and mechanical properties, such as tensile modulus (E). break stress (sigma(brk)), percent break strain (epsilon(brk)) and ductility(J), using wide-angle X-ray diffraction, transmission electron microscopy, differential scanning calorimetry (DSC), thermogravimetric analysis (TGA) and tensile and impact tests. RESULTS: Intercalated nanocomposites were formed even in the presence of 16 wt% clay (high loading) in PMMA matrix. PMMA intercalated into the galleries of the organically modified clay, with a change in d-spacing in the range 11-16 angstrom. TGA results showed improved thermal stability of the nanocomposites. The glass transition temperature (T-g) of the nanocomposites, from DSC measurements, was 2-3 degrees C higher than that of PMMA. The ultimate tensile strength and impact strength decreased with increasing clay fraction. Tensile modulus for the nanocomposites increased by a significant amount (113%) at the highest level of clay fraction (16 wt%) studied. CONCLUSION: We show for the first time the formation of intercalated PMMA nanocomposites with alkylammonium-modified clays at high clay loadings (> 15wt%). Tensile modulus increases linearly with clay fraction, and the enhancement in modulus is significant. A linear correlation between tensile strength and strainat-break is shown. Thermal properties are not affected appreciably. Organoclay can be dispersed well even at high clay fractions to form nanocomposites with superior bulk properties of practical interest. (c) 2007 Society of Chemical Industry.
Keywords: impact strength; mechanical properties; Nanocomposites; PMMA; Thermal properties

Critical organic modifier aliphatic tail length for the formation of poly(methyl methacrylate)-montmorillonite nanocomposites - Tiwari, Rajkiran R.; Natarajan, Upendra (Polymer Engineering and Science, 2020)
In this article, we report the influence of organic modifier structure (alkyl chain length C8-C20, single vs ditallow) and thereby, the effect of hydrophobicity on the structure, thermal and mechanical properties of poly(methyl methacrylate) (PMMA)-clay hybrids. Melt processed PMMA-clay hybrids were characterized using wide-angle X-ray diffraction, transmission electron microscopy, and differential scanning calorimetry. The organoclays having an alkyl chain length of more than 12 CH2 groups resulted in the formation of nanocomposites. The glass transition temperature (T-g) of PMMA increased in the presence of clay. The mean-field lattice model was used to predict the free energy for nanocomposite formation, which showed a reasonable match with the experimental results and provided a general guideline for the proper selection of polymer and organoclay (ie, organic modifier) to obtain nanocomposite. Tensile modulus showed maximum improvement of 58% for the nanocomposites compared to 9% improvement for the composites. Tensile modulus increased with increases in the alkyl chain length of the organic modifier and clay loading. The level of improvement for the tensile properties of nanocomposites prepared from primary and secondary ammonium-modified clay is the same as that obtained with the commercial organoclays.
Keywords: hybrid; mechanical properties; Montmorillonite; Nanocomposites; organoclay; poly(methyl methacrylate)